الكلمات الساساكية ذات أصل عربي في معجم اللغة الساسكية الإندونيسية - Salman Abu Al-Khair; Jajat Sudrajat (Rayah Al-Islam, 2018)
The study used an analytical descriptive method that described the right subject, with this method the researcher was able to describe the vocabulary of the Sasak language from Arabic (from the letter S to Z) in the Sasak - Indonesian dictionary and followed by analysis of each word in the form of a formula and its meaning so that these words can be utilized in teaching Arabic according to the variations of the words. Study result prive: 1) Whereas in the Sasak-Indonesian dictionary there are 91 Sasak language vocabularies from Arabic (letter S to Z). 2) Based on the available data, there are four forms of meaning changes in the absorption words from Arabic into the Sasak language, namely: Arabic vocabulary which contains the same meaning in Sasak language, Arabic vocabulary which has expanded meaning in Sasak language, Arabic vocabulary who experienced a narrowing of meaning in Sasak language vocabulary that experienced a change in meaning in Sasak language. 3) These absorption words can be used for teaching Arabic for the Sasak tribe in various ways and methods.